Ultraporous nanofeatured PCL–PEO microfibrous scaffolds enhance cell infiltration, colonization and myofibroblastic differentiation. Issue 36 (26th August 2015) - Li, Yan-Fang; Gregersen, Hans; Nygaard, Jens Vinge; Cheng, Weilu; Yu, Ying; Huang, Yudong; Dong, Mingdong; Besenbacher, Flemming; Chen, Menglin
Abstract : Ultraporous nanofeatured microfibers enhanced cell infiltration and nano-lamellae structured microfibers drasticly stimulated myofibroblasts differentiation. Abstract : In the field of tissue engineering, integration of micro-porosity, nano-topogaphical features and weattability into one three-dimensional (3D) scaffold remains a challenge. The extracellular matrix (ECM) mimicking feature of electrospun fibers endows them wide applications in tissue engineering. However, the tight-packing of electrospun submicron fibers hinder cell infiltration and further colonization. In this study, we fabricated hydrophilic, micro-porous scaffolds with nano-topographical cues by one-step electrospinning, and investigated NIH3T3 fibroblasts cell infiltration, colonization and myofibroblastic differentiation. The hierarchical porosity enhanced cell infiltration and proliferation significantly. Besides, the nano-topography influenced the cell actin distribution and cell morphology that stimulated myofibroblastic differentiation in a drastically different manner from that of traditional solid, smooth electrospun fibers, which may hold great potential in reconstructing tissues that require strong contractile forces.